Systematic review of flipped classroom in EFL reading teaching and learning / Yao Juan and Dr. Revathi Gopal - Yao, Juan; Gopal, Revathi (Universiti Teknologi MARA, Kedah, 2025)
In the realm of English as a Foreign Language (EFL) reading instruction, the flipped classroom approach has recently become a prominent and widely examined subject in educational research. Nonetheless, despite the growing interest in this area, previous studies have not thoroughly analyzed the implementation of the flipped classroom method in EFL reading instruction and learning from a systematic review perspective. The aim of this study is to explore the current trends and significant findings related to the use of the flipped classroom method in EFL reading instruction and learning. To accomplish this, 34 articles concerning the flipped classroom approach in EFL reading instruction and learning, published from 2014 to 2024, were retrieved from databases including Scopus, Science Direct, and Wiley Online. A systematic review methodology was utilized, with the articles being analyzed through a content analysis approach. The findings suggest that interest in the flipped classroom method increased among researchers in EFL reading instruction and learning following 2015, particularly with a significant rise in studies from 2020 to 2022. Furthermore, the majority of studies utilized mixed and quantitative research methods. Further research is necessary to evaluate the effects of the flipped classroom method in vocational college EFL reading classrooms. Further analysis revealed both the challenges and benefits linked to the flipped classroom method in EFL reading instruction and learning. The studies examined particularly emphasized the advantages of this approach in terms of its effectiveness. Based on this review, several recommendations are offered for practitioners and future research initiatives.